DESKRIPSI KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM PENYELESAIAN PERMASALAHAN PROGRAM LINIER - Maduni Ismu Qolbi; Indrie Noor Aini (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2022)
This study aims to describe the mathematical communication skills of high school students in class XI on linear program material. The research method used is descriptive research. The subjects in this study consisted of 5 students of class XI one of the public high schools in Karawang Regency which were determined using purposive sampling technique. The research data collection technique was obtained from a test instrument in the form of 3 validated description questions which contained 3 indicators of mathematical communication ability. The results of this study indicate that the mathematical communication ability of class XI high school students in Karawang Regency in understanding linear programming material is still very low. This can be seen from the average percentage of the three questions of mathematical communication skills is 48.3℅. In indicator 1, students have not been able to express mathematical ideas through writing, demonstrate and visually describe them. For indicator questions 2 students are able to understand, interpret, and evaluate mathematical ideas both in writing and in other visual forms, but there are still some errors. Meanwhile, on indicator questions 3 students have not been able to use terms, notations, mathematical symbols and their structures to present ideas, describe relationships with various situation models.